In the Balance: Weighing Preferences of Decisionally Incapacitated Patients - Guidry-Grimes, Laura (The Hastings Center report, 2018)
In this issue of the Hastings Center Report, Jason Wasserman and Mark Navin argue that patients without decisional capacity can still have relatively stable wishes or inclinations toward one treatment option over another and that these preferences are “not devoid of moral weight and might therefore guide or at least influence treatment decisions when they cannot be defeated by other considerations.” This position is not controversial among most bioethicists. The hard work comes in sussing out the details of this position. How much moral weight do these preferences have? When should preferences be defeated by other considerations? How should we identify actual preferences, and how should preferences be differentiated and weighed against one another?